Antifungal Effects of Saponin Extract from Rhizomes of Dioscorea panthaica Prain et Burk against Candida albicans. (29th April 2018) - Yang, Longfei; Liu, Xin; Zhuang, Xinming; Feng, Xuechao; Zhong, Lili; Ma, Tonghui
Abstract : Candida albicans is the most common fungal pathogen causing serious diseases, while there are only a paucity of antifungal drugs. Therefore, the present study was performed to investigate the antifungal effects of saponin extract from rhizomes of Dioscorea panthaica Prain et Burk (Huangshanyao Saponin extract, HSE) against C. albicans . HSE inhibits the planktonic growth and biofilm formation and development of C. albicans . 16–64 μ g/mL of HSE could inhibit adhesion to polystyrene surfaces, transition from yeast to filamentous growth, and production of secreted phospholipase and could also induce endogenous reactive oxygen species (ROS) production and disrupt cell membrane in planktonic cells. Inhibitory activities against extracellular exopolysaccharide (EPS) production and ROS production in preformed biofilms could be inhibited by 64–256 μ g/mL of HSE. Cytotoxicity against human Chang's liver cells is low, with a half maximal inhibitory concentration (IC50 ) of about 256 μ g/mL. In sum, our study suggested that HSE might be used as a potential antifungal therapeutic against C. albicans .